Efficacy of a topical polyphenol-based formulation in palmoplantar psoriasis: an observational study - Simone Amato; Annunziata Dattola; Luigi Bennardo; Martina Tolone; Steven Paul Nisticò (Dermatology Reports)
This single-arm observational study evaluated the efficacy and safety of a novel topical formulation containing a complex mixture of polyphenols (CMP) – a proprietary blend rich in oleocanthal and oleuropein aglycone (each >60%), along with hydroxytyrosol and other extra virgin olive oil (EVOO)-derived polyphenols – combined with triticum vulgare germ (TVG) oil, betaine, propanediol, and tocopheryl acetate in patients with mild palmoplantar psoriasis (PPP). Twenty participants (aged 20-55) applied the formulation twice daily for 8 days, with assessments conducted on days 0 (baseline), 5, and 8. Participants underwent a 60-day follow-up to assess the durability of benefits and potential late-onset adverse events. Clinical evaluations measured lesion extent, keratinization, inflammation, desquamation, and infiltration. A patient-reported questionnaire evaluated quality of life (QoL) and symptom burden. By day 8, the mean lesion extent had decreased by approximately 40%, inflammation had improved by about 50%, and desquamation had resolved fully in most cases. Patient-reported outcomes improve alongside clinical measures. At day 60, these improvements persisted in 85% of participants, and no adverse events emerged. The formulation’s mechanism of action is hypothesized to involve the concerted antioxidant and anti-inflammatory activities of polyphenols (oleocanthal, oleuropein aglycone, and hydroxytyrosol) in synergy with TVG oil’s supportive lipid matrix and other excipients. These findings suggest that EVOO-derived polyphenols formulated in TVG oil may serve as a valuable adjunct for managing PPP with good tolerability and sustained benefits.